Counseling for the man with severe male infertility. Issue 1 (7th January 2023) - Belladelli, Federico; Muncey, Wade; Seranio, Nicolas; Eisenberg, Michael L.
Abstract : Purpose of review: This review summarize the proper counseling for men with severe male factor infertility. Recent findings: Men who are experiencing infertility should have a semen analysis, the results of which may imply additional investigations, including genetic and hormonal. Moreover, possible modifiable factors that may harm men's reproductive health should be carefully evaluated. Finally, different treatment options are available. Summary: Approximately 15% of couples struggle with infertility. Complete evaluations of both men and women are required to determine the etiology of infertility and determine appropriate treatment.